Analisis Faktor Pengusaha Kuliner Menggunakan Jasa Iklan Instagram "Jakul Semarang" Sebagai Endorser - Amanda Ayu ` Dani; Sentot Suciarto A. (JEMAP, 2018)
Culinary Businessman uses advertising service like Jakul Semarang Instagram as endorser. Sample chosen for this research were 65 respondents by purposive sampling. Based on factor analysis, it was found that some factors pushing some businessmen in Semarang City to promote at Jakul Semarang included endorser account credibility, endorser characteristic, product picture which liked by follower, and endorser effectiveness. The dominant factor was endorser account credibility. There were four variables in this factor namely number of followers’ and likers’ credibility, the easily known hashtag, the simplicity of endorser performance, and the number of likers per picture.